The effects of 8-week complex training on lower-limb strength and power of Chinese elite female modern pentathlon athletes - Qiao, Zining; Guo, Zhenxiang; Li, Bin; Liu, Meng; Miao, Guozhen; Zhou, Limingfei; Bao, Dapeng; Zhou, Junhong (Frontiers in Psychology, 2022)
Complex training (CT) is a combination training method that alternates between performing high-load resistance training (RT) and plyometric training within one single session. The study aimed to examine the effects of CT on lower-limb strength and power of elite female modern pentathlon athletes under the new modern pentathlon format and competition rules. Ten female participants (age: 23.55 ± 2.22 years, weight: 60.59 ± 3.87 kg, height: 169.44 ± 4.57 cm, and training experience: 6.90 ± 2.08 years) of the national modern pentathlon team completed 8 weeks of RT as followed by 8 weeks of CT, with 2 weeks of break. Then, the participants conducted 8 weeks of CT, which included RT combined with plyometric training (e.g., drop jump and continuous jump). All stages of training were designed by the linear strength training period theories, requiring participants to train twice for the first 4 weeks and three times for the second 4 weeks. The one-repetition maximum (1RM) of squat, isometric mid-thigh pull (IMTP), counter-movement jump (CMJ), squat jump (SJ), pre-stretch augmentation percentage (PSAP), and reaction strength index (RSI) were assessed before and after both RT and CT training. One-way repeated-measure ANOVA models revealed that the 1RM of squat was significantly improved (p < 0.001) after RT as compared to pre-RT. No significant improvement in IMTP (p = 0.055), CMJ (p = 0.194), SJ (p = 0.692), PSAP (p = 0.087), and RSI (p = 0.238) was not observed. After CT, 1RM of squat (p < 0.001), IMTP (p < 0.035), CMJ (p < 0.001), SJ (p < 0.008), RSI (p < 0.006) were significant improved as compared to pre-RT, post-RT and pre-CT, while significant improvements in PSAP were observed as compared to pre-RT (p = 0.003) and pre-CT (p = 0.027), but not to post-RT (p = 0.156). This pilot study showed the promise of CT following RT to improve lower-limb strength and power in elite female modern pentathlon athletes. The findings are worthwhile to be confirmed in future studies with larger sample size and randomized design.